Clinical and genetic characteristics of congenital muscular dystrophies (part 2) - P. A. Chausova; O. P. Ryzhkova; A. V. Polyakov (Нервно-мышечные болезни)
Dystroglycanopathy is one of the groups of congenital muscular dystrophies, the occurrence of which is associated with a disorder of α-dystroglycan glycosylation. To date, 18 genes responsible for the development of this condition are known. The 2nd part of this review presents the classification, phenotypic forms, clinical features, pathogenesis and etiology of this type of congenital muscular dystrophies. In addition, the issues of molecular diagnosis of congenital muscular dystrophies are considered and information on modern developments in the treatment of this pathology is provided.